1995
DOI: 10.1111/j.1467-9914.1995.tb00178.x
|View full text |Cite
|
Sign up to set email alerts
|

Labour Market Institutions and Flexibility in Italy

Abstract: The paper surveys three broad categories of labor market institutions in Italy: employment protection legislation unemployment benefit systems and wage bargaining arrangements In each w e the recent evolution and current state of Italian institutions are evaluated and compared With those in other major European countries

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 13 publications
0
17
0
1
Order By: Relevance
“…7 The mandatory intervention of the Ministry of Labour in cases where prior consultation fails to reach agreement may impart a 'anti-dismissal' bias in the system, especially in cases where large firms are concerned. Although there has been no empirical work assessing the impact of these rules on employment in Greece, evidence from Italy -where dismissal rules are also strict -has shown that firing costs have been an important factor in slowing down adjustment of the work force (see the discussion in Demekas 1995).…”
Section: International Comparisons and A Preliminary Assessmentmentioning
confidence: 97%
See 1 more Smart Citation
“…7 The mandatory intervention of the Ministry of Labour in cases where prior consultation fails to reach agreement may impart a 'anti-dismissal' bias in the system, especially in cases where large firms are concerned. Although there has been no empirical work assessing the impact of these rules on employment in Greece, evidence from Italy -where dismissal rules are also strict -has shown that firing costs have been an important factor in slowing down adjustment of the work force (see the discussion in Demekas 1995).…”
Section: International Comparisons and A Preliminary Assessmentmentioning
confidence: 97%
“…CH04DEMA.QXD 9/25/07 1:38 AM Page 101 Sources: Own calculations; Demekas (1995);and Layard, Nickell and Jackman (1991).…”
Section: The Greek Labour Marketmentioning
confidence: 99%
“…Disability pensions have been used as Demekas 1995;INPS 1995;Del Boca 1995;Confindustria 1995;Guarna 1994 assistance benefits in a biased way, thanks to their relatively lax eligibility requirements. Social benefits for the needy -usually the elderly -are provided by local authorities, with the benefit levels and duration varying widely across regions.…”
Section: A Large Number Of Benefits and A Differential Treatment Of Wmentioning
confidence: 99%
“…Finally, according to the 1993 Pact, the regional-level bargaining is substituted for company-level bargaining in those regions where small companies (SMEs) predominate. This helps the unions to solve the problem of the lack of coverage of collective bargaining and union presence in SMEs (Demekas, 1995).…”
Section: Formalization and Controlled Decentralization Of Collective mentioning
confidence: 99%